Obesity epidemic through the prism of evolutionary processes - O. T. Kim (Кардиоваскулярная терапия и профилактика, 2022)
Currently, obesity has become one of the most serious public health problems. It takes millions of lives worldwide every year due to its association with numerous diseases and leads to significant social and economic losses. It is generally accepted that obesity is the result of the interaction of genes and environment, and the predisposition to it lies in our evolutionary past. This review discusses the role of adipose tissue in human evolution, the factors specifying a person’s predisposition to obesity, the main hypotheses for obesity origin, and potential prevention and treatment strategies arising from them. The evolutionary significance of visceral adipose tissue and some ethnic and sex characteristics associated with its distribution are also considered.